NIR persistent luminescence nanoparticles based turn-on aptasensor for autofluorescence-free determination of 17β-estradiol in milk. (30th March 2022) - Zhang, Yi; Zhou, Jie; Zhang, Xiao-Xiao; Wang, Wen-Long; Yang, Cheng; Shi, Xueli; Feng, Yong-Wei; Abdurahman, Renagul
Highlights: A NIR phosphorescence aptasensor without background fluorescence for the detection of 17β-estradiol was developed. NIR PLNPs and MoS2 nanosheets based turn-on aptasensor was used to improve S/N. The aptasensor exhibited sensitivity and selectivity for 17β-estradiol in complex milk samples. Abstract: Consistent exposure to 17β-estradiol through drinking water and food can cause health problems. Although many simple and sensitive fluorescence sensors of 17β-estradiol have been reported, most of them are based on fluorescence quenching test mode working in visible light range, which are inferior in anti-interference ability and quantitative range. Here, we developed a near-infrared (NIR) phosphorescence aptasensor for the detection of 17β-estradiol that has no background fluorescence. The aptasensor was based on Foster resonance energy transfer (FRET) between aptamer conjugated NIR persistent luminescence nanoparticles (PLNPs-Apt) and MoS2 nanosheets. The 17β-estradiol was quantified by the recovery of PLNPs' phosphorescence. This assay can detect 17β-estradiol in 0.5 mL samples with the LOD of 0.29 ng mL −1 and in concentrations of more than three orders of magnitude (from 0.5 ng mL −1 to 1.2 μg mL −1 ). This aptasensor exhibited selectivity for 17β-estradiol and was applicable in complex milk samples.